Sosialisasi Politik DPD PKS Kota Medan Pada Pemilu Legislatif 2009 - RAMADHAN, ISMUHAR (Politeia: Jurnal Ilmu Politik, 2013)
Political socialization is important in general election. Itâs effects wheather the vote would be good or bad. Partai Keadilan Sejahtera also do this way to influence voters. This study discuss-es about the method of DPD Partai Keadilan Sejahtera Kota Medan to successful legislative election in 2009. This study found there are three important method, that implemented by the the Partai Keadilan Sejahtera in political socialization. First, visit the community directly, par-ticular to each residence. Second, utilizing the approach of religious organizations; Third, uti-lizing the missionary activities in the mosques. The method this study is used qualitative de-scriptive. Colecting data of this study is using field research, eg. interview. The analysis using descriptive analysis techniques.Keywords: Political party, Election, Political socialization.